Neurobiological effects of transcranial direct current stimulation in younger adults, older adults and mild cognitive impairment. (4th March 2019) - Emonson, M.R.L.; Fitzgerald, P.B.; Rogasch, N.C.; Hoy, K.E.
Abstract: Transcranial direct current stimulation (tDCS) has been investigated as a way to improve motor and cognitive functioning, with largely variable results. Currently, relatively little is known about the neurobiological effects, and possible drivers of variability, in either healthy or clinical populations. Therefore, this study aimed to characterise the neurobiological effects to tDCS in younger adults, older adults and adults with mild cognitive impairment (MCI), and their relationship to cognitive performance. 20 healthy younger adults, 20 healthy older adults and 9 individuals with MCI participated in the study. All completed neuropsychological tasks and TMS-EEG, prior to and following delivery of 20 min of anodal tDCS to the left dorsolateral prefrontal cortex (DLPFC). EEG was also recorded during the 2-Back working memory task. Following tDCS, younger adults demonstrated alterations in early TMS-Evoked Potentials (TEPs), namely P30 and P60. Both younger and older adults exhibited a larger task-related N250 amplitude after stimulation, with contrasting relationships to cognitive performance. The MCI group showed no change in TEPs or ERPs over time. Comparisons between the groups revealed differences in the change in amplitude of early TEP (P60) and ERP (N100) peaks between younger and older adults. Our findings indicate that tDCS was able to modulate cortical activity in younger and older healthy adults, but in varying ways. These findings suggest that varied response to tDCS may be related to factors such as age and the presence/absence of cognitive impairment, and these factors should be considered when assessing the effectiveness of tDCS in healthy and pathological aging. Highlights: TMS-evoked (TEP) and event-related potentials (ERP) post-tDCS in young, old and MCI. Younger adults showed change in TEPs and ERPs, and older ERPs only following tDCS. MCI demonstrated no change in TEPs or ERPs, but comparable behavioural performance. Varied response to tDCS may be driven by age and presence of cognitive impairment.